Effect of a non-woven fabric covering on the residual activity of pendimethalin in lettuce and soil - Jursík, Miroslav; Kováčová, Jana; Kočárek, Martin; Hamouzová, Kateřina; Soukup, Josef (Pest management science, 2017)
BACKGROUND: Lettuce (Lactuca sativa L.) is a crop that is very sensitive to herbicide contamination owing to its short growing season. The use of long-residual herbicides and non-woven fabric coverings could therefore influence pendimethalin concentrations in soil and lettuce. RESULTS: The pendimethalin half-life in soil ranged between 18 and 85 days and was mainly affected by season (i.e. weather), and especially by soil moisture. Pendimethalin degradation in soil was slowest under dry conditions. A longer pendimethalin half-life was observed under the non-woven fabric treatment, but the effect of varying application rate was not significant. Pendimethalin residue concentrations in lettuce heads were significantly influenced by pendimethalin application rate and by non-woven fabric cover, especially at the lettuce's early growth stages. The highest pendimethalin concentration at final harvest was determined in lettuce grown on uncovered plots treated with pendimethalin at an application rate of 1200 g ha(-1) (7-38 µg kg(-1) ). Depending on growing season duration and weather conditions, pendimethalin concentrations in lettuce grown under non-woven fabric ranged from 0 to 21 µg kg(-1) . CONCLUSION: Use of transparent non-woven fabric cover with lettuce can help to reduce application rates of soil herbicides and diminish the risk of herbicide contamination in the harvested vegetables. © 2016 Society of Chemical Industry.
Keywords: salát (hlávkový); Soil; textilie; Aniline Compounds; půda; Pesticide Residues; Textiles; Lactuca; rezidua pesticidů; aniliny